Investigation on the superplasticity behavior of ultrahigh carbon steel - Özdemir, N; Orhan, N (Elsevier Sci Ltd, 2006)
In this study, the superplasticity behavior of grain-refinement ultrahigh carbon (UHC) steel with thermomechanical process and having an average grain size of 3 gm was investigated at the eutectoid transformation points of this material with the stepped strain rates between 2 x 10(-3) and 1.6 x 10(-2) s(-1) test method. The results showed that the best superplasticity was obtained at 735 degrees C and in the deformation rate range between 3.3 x 10(-3) and 4.6 x 10(-3) s(-1). The deformation rate sensitivity exponent, m, was calculated as 0.58 in this range. (C) 2005 Elsevier Ltd. All rights reserved.
Keywords: superplasticity; UHC steel; grain-refinement; thermomechanical treatment; hot deformation